The Restoration and the England of Charles II - Miller, John (Longman, 1997)
Chronicles the twenty-five year reign of Charles II under whose rule Parliament kept most of the powers it had won under Cromwell and shared governing authority with the king
96-50299
Keywords: Great Britain; History; Charles II; 1660-1685; 1660-1688